Systematizing dark personality traits within broader models of personality. (February 2022) - Rogoza, Radosław; Kowalski, Christopher Marcin; Saklofske, Donald H.; Schermer, Julie Aitken
Abstract: Previous research has attempted to derive arguments for the categorization of traits as 'dark' without theoretical justification or rationalizations. We begin with a description of current conceptualizations of the darkness of traits followed by a new perspective on the catalogue of dark personality traits and the theoretical boundaries of different shades of darkness within the broader personality structure. Finally, we address the redundancy problem observed within the field on dark personality traits. Our analyses are offered as a guide to future research towards a more parsimonious and useful set of criteria (a "compass" of sorts) for inclusion within the "dark" cluster. Highlights: We define dark personality traits. We present the catalogue of dark personality traits. We solve the redundancy problem of psychopathy and Machiavellianism.